2016
DOI: 10.1002/jcp.25626
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria‐Targeted Antioxidants and Uncouplers of Oxidative Phosphorylation in Treatment of the Systemic Inflammatory Response Syndrome (SIRS)

Abstract: Systemic inflammatory response syndrome (SIRS) development is accompanied by mitochondrial dysfunction and excessive ROS production. Mitochondrial dysfunctions also occur in many SIRS-related diseases and may be critical for their pathogenesis; therefore, a use of mitochondria-targeted drugs is a promising trend in SIRS research and therapy. Here, we review recent studies concerning the application of the mitochondria-targeted antioxidants and uncouplers of oxidative phosphorylation in animal models of SIRS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 103 publications
0
11
0
Order By: Relevance
“…Mitochondria are one of the most important sources of ROS in the cells and it was shown that Tat could perturb the normal mitochondrial function that in turn could regulate the redox state of the cells [78] , [79] , [80] . To test whether Tat induced mitochondrial ROS production in B-cells, we used rotenone (10 µM), an inhibitor of the mitochondrial complex I, SkQ1 (20 ng/ml), a specific mitochondria-targeting antioxidant [81] , [82] and 2,4-dinitrophenol (DNP) (10 µM), an uncoupler of oxidative phosphorylation [83] . We treated B-cells with these different molecules simultaneously with 250 ng/ml Tat for 6 h and observed that Tat-induced ROS production was inhibited in their presence to the control levels, indicating that mitochondria were a source of ROS in Tat-treated cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mitochondria are one of the most important sources of ROS in the cells and it was shown that Tat could perturb the normal mitochondrial function that in turn could regulate the redox state of the cells [78] , [79] , [80] . To test whether Tat induced mitochondrial ROS production in B-cells, we used rotenone (10 µM), an inhibitor of the mitochondrial complex I, SkQ1 (20 ng/ml), a specific mitochondria-targeting antioxidant [81] , [82] and 2,4-dinitrophenol (DNP) (10 µM), an uncoupler of oxidative phosphorylation [83] . We treated B-cells with these different molecules simultaneously with 250 ng/ml Tat for 6 h and observed that Tat-induced ROS production was inhibited in their presence to the control levels, indicating that mitochondria were a source of ROS in Tat-treated cells ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Excessive inflammatory reactions may result in the development of fatal multiple organ failure. The important role of mitochondrial ROS in SIRS was reviewed recently [60].…”
Section: Structure and Functions Of Mitochondriamentioning
confidence: 99%
“…Although the clinical application of antioxidants for skin inflammatory disorders is not widespread, we wanted to test it using a combination of natural molecules. Consequently, EP2311454 treatment main components are resveratrol, taurine and ascorbyl-Lpalmitate previously defined as antioxidant in humans and indomethacin which is anti-inflammatory in low doses associated to several human diagnosis (20,21). The aim of this study is evaluate the clinical efficiency of the treatment in moderate and severe AD patients whereas mild AD patients have a better treatment.…”
Section: Discussionmentioning
confidence: 99%